In situ synthesis of dicobalt phosphide on tungsten carbide-cobalt cemented carbide substrates as a hydrogen evolution reaction electrocatalyst. (November 2021) - Han, X.Q.; Lin, N.; Chen, M.; Wang, Z.Y.; Tang, Y.; Ma, C.
Abstract: A new approach is proposed to recycle tungsten carbide-cobalt cemented carbides through fabricating dicobalt phosphide catalyst on the surface of cemented carbides for the hydrogen evolution reaction. tungsten carbide-cobalt cemented carbides with different tungsten carbide grain sizes were prepared via a powder metallurgy method. The three-dimensional cobalt skeletons with controlled pore structure on the surface of cemented carbides were obtained by etching tungsten carbide grains in alkaline solution. Dicobalt phosphide particles were synthesized on the cobalt skeleton via a phosphorization treatment. The increasing pore size of cobalt skeletons significantly improved the catalytic performance of phosphatized sample. The design and preparation of dicobalt phosphide catalyst can recycle waste cemented carbides. Graphical abstract: Image, graphical abstract